Science and Technology Policies and the Middle-Income Trap: Lessons from Vietnam. - Klingler-Vidra, Robyn; Wade, Robert (Journal of Development Studies, 2020)
As Vietnam crossed the World Bank's threshold from 'low income' to 'lower middle-income' in 2010 the government and aid donors started to speak about 'the middle-income trap' as a central problem; and to frame 'science and technology (S&T) policy' as a means of sustaining economic growth and thereby avoiding the trap. They identified China and its S&T policy as a model, and pointed to Intel's $1 billion facility as evidence of a burgeoning technology hub. Yet in the years that followed, Vietnam's S&T policy has limped along, with efforts simply to boost the number of Silicon Valley-styled start-ups rather than to pursue a 'Made in China 2025'-like programme. This paper reveals two main reasons. First, the Ministry of Science and Technology is a weak ministry with little budget, unable to persuade other ministries to cooperate in more ambitious and capital-intensive strategies. Second, excitement around S&T policies was fuelled by an influx of high-tech Vietnamese returning home after the 2008 Global Financial Crisis, lending support for building start-up ecosystems. These mechanisms are reinforced by Western aid agencies' support for this narrow S&T policy conception. Findings are based on policy documents and interviews conducted with S&T policy-makers, aid donor staff, and start-up investors between 2012 and 2018.